Computational aeroacoustic study of a landing gear - Khanal, Bidur; Knowles, Kevin; Saddington, Alistair J.; Obayashi, S. (Cranfield University, 2009)
Computational study of a single wheel landing gear con guration was completed to understand the noise source and it's nature. The ow eld visualisation showed the present of large structural shedding in the wake side of the the landing gear wheel. These large structures were responsible for the low frequency noise. Spectral peaks at frequencies lower than 200 Hz were found to exist from the analysis of the frequency content of the pressure signals at far eld. These low frequency peaks were due to the large structural shedding.
Keywords: Flow Dynamics; Aeroacoustic; Aerodynamics; Aerodynamic noise; Airplanes - Landing gear - Design and construction